Biliary atresia at Red Cross War Memorial Children's Hospital: A retrospective descriptive study reviewing the age of presentation, clinical course and outcome of infants presenting to RCWMCH with biliary atresia - Levin, Lindsey Nicola (Department of Paediatrics and Child Health, 2017)
Background: Biliary atresia (BA) is a progressive obstructive cholangiopathy of unknown aetiology, occurring during the perinatal period. If left untreated it rapidly progresses to hepatic fibrosis and cirrhosis, with death occurring within 2 years. It is the leading cause of end-stage liver disease in the paediatric population and remains the most common indication for paediatric liver transplantation in South Africa. Objectives: Despite a wealth of information from developed countries, very little information is available in Africa and other developing nations. This study aimed to describe the age of presentation, clinical course and outcome of infants presenting to Red Cross War Memorial Children's Hospital (RCWMCH) with BA. Methods: A retrospective folder review was conducted on all patients with BA presenting to RCWMCH between January 2003 and December 2013. The main outcomes assessed were median time to presentation to tertiary services, clearance of jaundice post Kasai procedure (bilirubin <20μmol/L) and 2- and 5-year overall survival (OS) and survival with native liver (SNL). Results: The median age at presentation in the 80 cases reviewed was 70 days. Kasai procedure (KP) was performed in 62 (77.5%) patients at a median age of 68 days. 18 patients who presented late did not undergo KP. Clearance of jaundice was achieved in 39% of KPs. 13 patients underwent KP beyond 90 days with a success rate of 38%. 2- and 5-year SNL rates were 41% and 37.5% respectively with OS of 59% at 2-years and 56% at 5-years. Liver transplant was only performed in 12 of the 54 patients who showed progression to require transplantation. Conclusions: Jaundice clearance post KP and SNL compared favourably with international figures, however, lower overall survival rates reflected lack of access to transplantation. Age at KP was not a predictor of poor outcome.